NILAI BUDAYA WALIMAH PERKAWINAN (WALIMATUL ‘URUSY) DALAM PEMBERDAYAAN EKONOMI MASYARAKAT (Studi Kasus di Kelurahan Gondorio Ngaliyan Semarang) - Muyassarah Muyassarah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aims to know the culture walimah marriage (walimatul ‘urusy) inSemarang Gondorio economic empowerment. Data collection methods, the methods of documentation, observation, interview and literature search literature. In order to keep the scientific interpretation, taken by way of reflective thinking, meaning pacing between deduction and induction. The findings of this study are: Invitation walimah marriage (walimatul ‘urusy) implemented before the ongoing Islamic marriage contract, to ask for their blessing and tahlil. The husband and wife donate everything, so that people who have a celebration not a lot of debt or burden. Culture delehi implemented in walimah marriage (walimatul ‘urusy), to lighten the load and save. Culture ceting implemented in walimah marriage (walimatul ‘urusy), in order to have a celebration that can provide snacks to guests. Culture walimah marriage in Gondorio able to empower the local economy.